ANALISIS ARUS KAS SEBELUM DAN SESUDAH PANDEMI COVID-19 PADA BADAN PENGELOA TAMANSARI MAHOGANY APARTEMEN PERIODE 2019-2023 - Karlina Yuliana; Wike Pertiwi; July Yuliawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study was to compare the cash flow situation at the Tamansari Mahogany Apartment Management Agency before and after COVID-19. This study used a qualitative descriptive methodology based on cash flow data, gathering information through documentation and interviews with the chief financial officer, chief tenant relations officer, and building manager. The study's findings are as follows: 1) Cash flow in 2019 prior to COVID-19 Due to the poor occupancy rate and numerous unit handovers that were empty or unoccupied, Tamansari Mahogany Apartments saw decreased income in 2019;2) Cash flow in 2020–2022 during COVID-19. The COVID-19 pandemic caused many homes to be used as locations for self-isolation for people infected with the virus, which resulted in a rise in income for Tamansari Mahogany Apartments from 2020 to 2022. 3) Cash flow in in 2023 a COVID-19 after COVID-19 Because Tamansari Mahogany Apartments work with agents to boost occupancy compared to COVID-19, they have constant and growing income. Establishing a successful and efficient company plan and concentrating on the allocated budget are crucial for organizations.